PEMBELAJARAN PENGELOLAAN KEUANGAN ORANG TUA, UANG SAKU, DAN HASIL BELAJAR TERHADAP LITERASI KEUANGAN DI SMK PGRI 3 SIDOARJO - Megasari, Is Rianda (UNIVERSITAS NEGERI SURABAYA, 2014)
This research purposed to analyze the influence of parental financial management learning on learning outcomes, pocket money on learning outcomes, parental learning financial management on financial literacy, allowance on financial literacy, the result of learning on financial literacy. Population of this research a student of class XI Accountancy is 168 student and the sample is 118 student. The methods of data collection is questionnaire, documentation and analysis techniques used SEM. The results showed learning financial management parental influence learning outcomes, pocket money has no effect learning outcomes, learning financial management of the parents has no effect financial literacy, money pocket effect financial literacy, learning outcomes influence financial literacy